A Brief Review on Conducting Polymer Nanocomposite Based Epoxy Coatings for Marine Applications. Issue 1 (March 2021) - Fitriya, A.M; Shahabuddin, Syed; Sridewi, Nanthini; Norsyarizad, M.; Pandey, A.K.
Abstract: Recently, fouling has become the main concern in the marine, naval and shipping industries. Furthermore, fouling has caused an increase in ship drag and fuel consumption whilst reducing the hydrodynamic performance of ships. Marine structures that partly or fully submerged such as oilrigs, submarine pipes and marine buoys are also impacted. Therefore, research and numerous studies had conducted to propose the best antifouling coating. The main objective of this review is to provide an overview of polymer-based surface coatings for protection from marine biofouling organisms. The physicochemical and mechanical properties of polymers had found to make these materials promising as polymeric coating that can be used in marine applications. Furthermore, this review will discuss the utilization of nanocomposites as additives, modifiers and nanofillers in order to enhance the properties of the polymer for antifouling coating.